Made in China: The international supply of illicit Semaglutide and weight-loss medicines online - Luke A. Turnock; Evelyn Hearne; Lambros Lazuras (Emerging Trends in Drugs, Addictions, and Health)
Background: The use of GLP-1 medicines for weight-loss purposes is increasingly widespread. While these drugs are available as prescription medicines in the UK, there is an expansive illicit market for their supply operating online. This study investigates the scope and impact of illicit weight-loss medicines supplied online through a scoping review of an e-commerce platform – Made-in-China.com – where a large number of Chinese-based sellers are advertising GLP-1 medicines and related weight-loss drugs to European consumers. Methods: The researchers undertook a preliminary examination of available product and supplier pages on Made-in-China.com through a search of 10 key terms relating to weight-loss medicines, and qualitative analysis of product and seller pages for the first 30 results returned for each term. Data from these pages was analysed thematically. All searches were conducted in a single month in 2024. Findings: document how the platform operates, including ease of access, the extent of weight-loss medicine listings offered, and how product is promoted by sellers, including warnings of product being ‘for research use’, as well as physique-related promotional imagery. We explore the potential harms of counterfeit semaglutide being sold in branded packaging that suggests it may be ‘legitimate’, as well as how sellers advertise their ‘legitimacy’ to potential buyers through details of shipping practices, images of lab equipment, and claims of lab tests to verify product quality. Discussion: We consider how public health policy should address the potential harms arising from this website, with particular focus on the easy access to counterfeit prescription-only medicines provided by platforms such as made-in-china.com, which are likely to be substandard and pose a potential risk to users. We also consider the difficulties of regulating international drug supply in the context of differing legal jurisdictions, and the need to educate the public on the risks of illicit market GLP-1 medicines.